The Effect Of E-Service Quality And E-trust On Repurchase Intention Through E-Word of Mouth (E-WOM) as an Intervening E-commerce Shopee on the Y Generation in Makassar City - Gracela Marisa Sanapang (Scientium Management Review, 2022)
The presence of e-commerce in the current era has made this new industry a very competitive sector with various offers being made to consumers. One of the main keys to success in running the e-commerce industry is the ability of sellers or manufacturers to offer online services related to quality, trust, and security for consumers in making online purchase transactions. E-commerce business actors will run a strategic business to attract consumers and make them buy repeatedly on e-commerce media so that consumer repurchase is one of the key factors in determining business profitability and sustainability. The intention to repurchase by consumers is influenced by several factors including e-service quality, e-trust, e-WOM, and repurchase intention. This study aims to analyze the effect of e-service quality on e-WOM, the effect of e-trust on e-WOM, the effect of e-service quality on repurchase intention, the effect of e-trust on repurchase intention, the effect of e-WOM on repurchase intention. the effect of e-service quality on repurchase intention through e-WOM and e-trust on repurchase intention through e-WOM on the e-commerce application media Shopee generation Y in Makassar city. This research is quantitative research with a survey method. The population of this study were all users of the Shopee e-commerce application media from generation Y in the city of Makassar and had made at least two transactions on the Shopee e-commerce application media. This research is not known the number of existing populations so the sampling method used is non-probability sampling with a type of sampling that is purposive sampling with a total sample of 384 respondents. The data collection technique uses a questionnaire that has been tested for validity and reliability. The data analysis technique in this study is Structural Equation Modeling (SEM) using Smart PLS to process the data. The results of the study show that e-service quality influences e-WOM and repurchase intention. E-trust influences e-WOM and repurchase intention. E-WOM influences repurchase intention. After that, e-service quality has an influence on repurchase intention through e-WOM, and also e-trust has an influence on repurchase intention through e-WOM.